PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS X MIPA SMAN 7 PADANG MELALUI PENERAPAN MODEL PEMBELAJARAN GUIDED INQUIRY - Muhammad Luthfi (Departemen Matematika, 2018)
A person’s ability to solve problems was a very important aspect that must be possessed by students’ in learningmathematics because it wa one of the goals of learning mathematics. However, result of observation and interviews in the class X MIPA SMAN 7 Padang shows that students’mathematical problem solving ability was still low. It was cause by students’ did not involvment in learning process and they didn’t accustomed to solve non routine problems. Therefore, to improvestudents’ mathematical problem solving ability required anappropriate strategy in learning activity. One of learning models that can be used is guided inquiry model. Purpose of study was to determine students’ mathematical problem solving ability that usingguided inquirylearning model and compare it with students’ who learn with conventional learning in class X MIPA SMAN 7 Padang year lesson 2017/2018. Based on data analysis at a = 0,05 by doing t’-test,it is obtained Pvalue = 0,000, because P-value < a then????0 rejected. This means that students’ mathematical problem solving ability who learning by applying guided inquiry model is better than conventional learning in class X MIPASMAN 7 Padang year lesson 2017/2018.Keywords – conventional learning, guided inquiry learning model, mathematical problem solving ability.